Peningkatan Kapasitas Guru BA KBBA Basin III Melalui Edukasi Kesehatan Skrining Tumbuh Kembang Anak Usia Pra Sekolah - setianingsih setianingsih; Istianna Nurhidayati; Fitriana Nugraheni (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Health education with the theme of developmental screening of pre-school children is a necessity, so that teachers have adequate knowledge and skills. SDIDTK is a basic and very easy effort to detect early delays in child development. Through early detection, deviations in children's growth and development can be seen. PAUD as a place of formal education for early childhood, the second place of growth and development stimulation after the family. To know the development that children have achieved, regular assessment of growth and development is needed so that it can be detected early and early stimulation and intervention can be carried out. So it is important for teachers to know about how to screen for early detection and intervention of child growth and development. With the implementation of health education on pre-school children's growth and development screening in BA Basin, it is proven to increase teachers' knowledge of screening and early detection of children's growth and development. The average knowledge before the health education was 10.71 points increased to 14.15 points.